Prevalence and risk factors of postpartum depression and adjustment disorder during puerperium – a retrospective research. (20th October 2021) - Ferrari, Barbara; Mesiano, Luca; Benacchio, Luca; Ciulli, Belinda; Donolato, Arianna; Riolo, Rossana
ABSTRACT: Objective: This observational study was designed to evaluate risk factors and distribution of Adjustment Disorder (AD) and Postnatal Depression (PPD), after delivery and a positive screening at Camposampiero Hospital (2012–2017). Background: After childbirth, women are vulnerable to develop psychological disorders. Since the effects of psychopathology are relevant, prevention and early intervention are of paramount importance. Recognising risk factors is therefore necessary. Methods: Women were screened after delivery, between the 6 th and 8 th week, using EPDS. Depressive symptoms were examined by psychological assessment. Socio-demographic, clinical and obstetric variables were analysed to identify women at greater risk for developing perinatal psychological disorders. Results: Of the 3102 women screened, 14.6% resulted positive: 23.6% of them suffered from AD and 5.5% from PPD. Regarding AD, previous induced abortion, unwanted pregnancy, unemployment and family history of mental disorders were the most relevant risk factors. Higher risks for PPD were: not attending antenatal classes, unwanted pregnancy, previous psychopathology and family history of mental disorders. Conclusion: In our study, distribution and risk factors for PPD and AD are in line with those reported in literature. Paying attention to subclinical symptoms co-related to items of EPDS helps healthcare professionals to be more sensitive in detecting suffering women.